Pengaruh Volume Media Tanam Terhadap Pertumbuhan Dan Hasil Tanaman Selada (Lactuca sativa L. - Alfons Versali; I Made Sukerta; Dewa Nyoman Raka (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
The cress (Lactuca sativa L.) is a horticultural plant that has a considerable selling prospect and value. The development of lettuce has the good prospect of supporting more people's nutrition, greater job opportunities, agribusiness development. The purpose of this study is to know how media volume affects the growth and production of lettuce. As for the benefit of this study, information to the community in particular about how the volume of soil on the growth and production of the lettuce plant can affect and provide effective soil volume information on growth and the product of the lettuce. The study used random group design methods (shelves). The study was conducted from May 26 to July 8 with six treatment, treatment of 40 g/5 kg (V1), 40 g/6 kg (V2), treatment of 40 g/7 kg (V3) treatment of 40 g/ 8 kg (V4), treatment of 40 g/9 kg (V5) and treatment of 40 g/ 10 kg (V6). In the test of media volume on the lettuce plant, application of media volume 40 g/ 5 kg soil results in the best growth on all the observable parameters: plant height (cm), leaf number (cm), root length (cm), total fresh weight (g), and total dry weight of the plant (g)